2018
DOI: 10.1177/0093650218797411
|View full text |Cite
|
Sign up to set email alerts
|

Love or Comprehension? Exploring Strategies for Children’s Prosocial Media Effects

Abstract: Given children’s difficulty comprehending prosocial narratives, we examined strategies to bypass comprehension (affiliative priming) and reduce cognitive burden (simplified lessons, adult scaffolding). In Study 1, one hundred seven 3- to 5-year-olds watched a prosocial narrative (helping vs. waiting) with affective primes (loving vs. funny) or a control narrative. Comprehension was low and behavioral outcomes were unaffected by lesson or prime. In Study 2, sixty-four 3- to 5-year-olds watched shorter stimuli (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 43 publications
0
14
0
Order By: Relevance
“…Notably, many of the programs examined feature music as a key didactic element (e.g., Barney, Sesame Street ). More recent work utilizing 1-min song videos from Daniel Tiger’s Neighborhood showed that brief exposure to a helping song increased children’s spontaneous helping, although more naturalistic exposure to longer content segments did not (Mares, Bonus, & Peebles, 2018). None of these studies specifically involved singing along with the musical stimuli, although some children may have done so.…”
Section: Impact Of Song Lyrics On Behavior In Children and Adultsmentioning
confidence: 99%
“…Notably, many of the programs examined feature music as a key didactic element (e.g., Barney, Sesame Street ). More recent work utilizing 1-min song videos from Daniel Tiger’s Neighborhood showed that brief exposure to a helping song increased children’s spontaneous helping, although more naturalistic exposure to longer content segments did not (Mares, Bonus, & Peebles, 2018). None of these studies specifically involved singing along with the musical stimuli, although some children may have done so.…”
Section: Impact Of Song Lyrics On Behavior In Children and Adultsmentioning
confidence: 99%
“…Mares et al. (2018) also found that exposing children to a song video about helping enhanced the likelihood that they engaged in helping behavior.…”
Section: Discussionmentioning
confidence: 98%
“…The authors suggest that their findings are at odds with the argument that reciting nursery rhymes is a shallow educational practice that only leads to encoding of surface material. Mares et al (2018) also found that exposing children to a song video about helping enhanced the likelihood that they engaged in helping behavior.…”
Section: Limitations and Future Directionsmentioning
confidence: 88%
See 1 more Smart Citation
“…Thus, prosocial media content is linked to more prosocial behaviors and adaptive emotional strategies (Coyne et al, 2018). One challenge, however, is that very young children often struggle to follow prosocial dialogues (Mares et al, 2022). The potential complexity of some prosocial content may mitigate the potential positive impact of prosocial content on children.…”
Section: Prosocial Contentmentioning
confidence: 99%